2012
DOI: 10.3168/jds.2011-4350
|View full text |Cite
|
Sign up to set email alerts
|

Sickness behavior in dairy cows during Escherichia coli mastitis

Abstract: The consequences of mastitis in terms of dairy cow behavior are relatively unknown. Future assessment of dairy cow welfare during mastitis will be facilitated by knowledge about the potential of mastitis to induce sickness behavior. Our aim was to examine behavior of dairy cows in the period from 2 d before (d -2 and -1) to 3 d (d 0, 1, and 2) after experimental intramammary challenge with Escherichia coli. Effects of experimentally induced mastitis on behavior were examined in 20 primiparous Danish Holstein-F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
106
5
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(123 citation statements)
references
References 25 publications
10
106
5
2
Order By: Relevance
“…Although we avoided surgical procedure for tissue collection and our biopsies were up to a 100-fold to a 1000-fold smaller than described by others, we did not avoid significant internal udder bleeding with our minimal invasive biopsy technique. The observation that bleeding in the udder could be related to pain is in accordance with findings reported by Fogsgaard et al (2012) who found a reduction in the cows' lying time in cows exposed to the biopsy procedure while investigating for sickness behavior.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Although we avoided surgical procedure for tissue collection and our biopsies were up to a 100-fold to a 1000-fold smaller than described by others, we did not avoid significant internal udder bleeding with our minimal invasive biopsy technique. The observation that bleeding in the udder could be related to pain is in accordance with findings reported by Fogsgaard et al (2012) who found a reduction in the cows' lying time in cows exposed to the biopsy procedure while investigating for sickness behavior.…”
Section: Discussionsupporting
confidence: 80%
“…Hence, it was possible to conduct liver and udder biopsies simultaneously in the same individual without causing any major disturbances to the systemic APR during disease, whereas some local inflammatory parameters are affected. E. coli mastitis often results in lower feed intake and milk production (Burvenich et al, 2003;Pezeshki et al, 2011;Fogsgaard et al, 2012). Both parameters were affected in this study after E. coli inoculation, and combined biopsying enhanced the effect on milk yield even further.…”
Section: Discussionmentioning
confidence: 69%
“…The adverse effects of illness on eating and rumination as well as the ameliorating effects of treatment are of primary clinical interest. It was shown that experimental intramammary challenge with Escherichia coli caused a decrease in rumination activity within 24 hours (Fogsgaard et al, 2012), and collection of a liver biopsy sample also led to reduced rumination, most likely because of pain (Mølgaard et al, 2012). Cows with left displacement of the abomasum (LDA) had significantly lower rumination activity, particularly fewer chewing cycles per regurgitated bolus, for five days after successful surgical correction, whereas eating variables did not differ between operated and healthy cows (Trösch, 2013;Braun et al, 2015c).…”
Section: Introductionmentioning
confidence: 99%
“…Signs of sickness behaviour can last several days after treatment of the cows (up to at least 10 days). Mastitic cows show decreased feeding time (Fogsgaard et al, 2012), decreased lying time (Cyples et al, 2012;Fogsgaard et al, 2012;Medrano-Galarza et al, 2012;Fogsgaard et al, 2014), which is interpreted as pain or soreness in the infected udder during lying, reduced rumination (Fogsgaard et al, 2012), reduced feed intake starting one or several days before the diagnosis of clinical mastitis (Bareille et al, 2003;Fogsgaard et al, 2014;Sepulveda-Varas et al, 2014a), and increased restlessness during milking, manifesting as kicking and tripping (Fogsgaard et al, 2014).…”
Section: Impact Of Mastitis On Welfarementioning
confidence: 99%